Purchase Decisions: The Impact of Quality, Beauty Influencers, and Brand Image - Nursarifah Dahyunita Putri; Budiman Abdulah (BALANCE: Economic, Business, Management and Accounting Journal, 2026)
Make Over is a premium local cosmetic brand widely known for its product quality and frequent collaborations with beauty influencers. Sales of Make Over products still lag behind those of other local brands, such as Wardah. This study aims to provide empirical evidence regarding the influence of product quality, beauty influencers, and brand image on consumer purchasing decisions for Make Over products in the Jakarta area. This study used a quantitative approach, with a small population and a sample of 230 respondents. Data collection was conducted through questionnaires, and the analysis method used was Structural Equation Modeling (SEM-PLS). The results showed that the three independent variables of product quality, beauty influencers, and brand image had a positive effect on purchasing decisions. Brand image had the most significant influence, indicating that a strong, consistent brand perception is crucial in shaping consumer purchasing behavior. The managerial implications of these results are that Make Over needs to ensure product quality remains the main attraction for consumers, select credible beauty influencers who match the characteristics of the target market (those who have used Make Over products and are aged 20-35 years), and strengthen the brand image through consistent visual communication and promotions